DNA-Dependent Protein Phosphorylation Activity in Xenopus Is Coupled to a Ku-Like Protein - KANUNGO, JYOTSHNABALA (Biol Bull, 1997)
DNA-dependent protein kinase (DNA-PK) is a nuclear enzyme and functions as a serine/threonine kinase that has been well characterized in both the human and the mouse. The regulatory subunit of DNA-PK is the Ku autoantigen. To demonstrate that a Ku-like protein is present in Xenopus oocytes, we used immunoprecipitation analysis with a monoclonal antibody raised against human Ku antigen and autoimmune serum containing anti-Ku antibodies. Metabolic labeling studies indicate that the Ku-like protein is synthesized mainly in late vitellogenic oocytes. By using a specific peptide substrate for DNA-PK, we demonstrate the activity of a DNA-dependent protein kinase in oocyte extracts. The kinase activity requires the Ku-like protein, since extracts depleted of Ku protein by immunoadsorption with human anti-Ku antibodies fail to demonstrate the DNA-dependent phosphorylation activity. The increased enzyme activity in vitellogenic oocytes may be correlated to the increased levels of Ku protein observed in these oocytes compared to the pre- and early vitellogenic oocytes.